METODE KISAH DALAM AL-QUR’AN DAN SUNNAH DAN URGENSINYA DALAM PENDIDIKAN KARAKTER - Bunyanul Bunyanul (Universitas Muhammadiyah Tangerang, 2019)
ABSTRACT وَأَنْ لَوِ اسْتَقَامُوا عَلَى الطَّرِيقَةِ لَأَسْقَيْنَاهُمْ مَاءً غَدَقًا“Dan bahwasanya: Jikalau mereka tetap berjalan Lurus di atas jalan itu (agama Islam), benar-benar Kami akan memberi minum kepada mereka air yang segar (rezki yang banyak)”. (Q.S. Al-Jin : 16) It is undeniable that education is a process that is very important and even most important for humans to achieve the degree of glory in the eyes of Allah SWT and all His creatures. But the education process is not an easy thing, even education is a complex process because it is a planned, systematic, structured effort and aims to develop, manage, foster, direct, and change humans who are multidimensional beings towards perfection. The process of education is the process of